1982
DOI: 10.1111/j.1365-3091.1982.tb01718.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative relationships between numbers of fluvial cycles, bulk lithological composition and net subsidence in a Scottish Namurian basin

Abstract: This detailed quantitative basin analysis of fluvial deposits in a subsiding Namurian structural basin is aimed at discovering underlying statistical relationships between numbers of fluvial cycles, bulk lithological composition and net subsidence which could be used as a background to future sophisticated computer simulation experiments and would also facilitate comparison with other ancient basins. The succession studied lies between two widespread marine bands, one of Arnsbergian (E2) and one of Kinderscout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…This synsedimentary subsidence is commonly recorded by thickened fluvial sequences made up of stacked fining-upward cycles (Read and Dean, 1982;Johnson, 1984) that show a high proportion of floodplain facies (Bridge and Leeder, 1979;Heller and Paola, 1996). The local base-level drop caused by the subsidence may lead to locally steep gradients and the development of degradation surfaces upstream and in the margins on the reaches affected by subsidence (Gardner, 1983;Snow and Slingerland, 1990;Hassan and Klein, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…This synsedimentary subsidence is commonly recorded by thickened fluvial sequences made up of stacked fining-upward cycles (Read and Dean, 1982;Johnson, 1984) that show a high proportion of floodplain facies (Bridge and Leeder, 1979;Heller and Paola, 1996). The local base-level drop caused by the subsidence may lead to locally steep gradients and the development of degradation surfaces upstream and in the margins on the reaches affected by subsidence (Gardner, 1983;Snow and Slingerland, 1990;Hassan and Klein, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Micro-scale and meso-scale sedimentary cycles are attributed to autogenic processes such as individual flood events and lateral channel accretion, whereas macro-scale cyclicity is attributed to a combination of autogenic and allogenic processes such as channel avulsion, regional climate change, and neotectonics (Kraus and Aslan 1999). Mega-scale alluvial cyclicity is often regarded as the product of allogenic processes such as tectonic activity and variable climate (e.g., Allen 1978;Read and Dean 1982;Blakey and Gubitosa 1984;Posamentier and Allen 1993;Legarreta and Uliana 1998;Kraus 2002). Although there is general agreement in the literature that eustatic sea-level change may also influence mega-scale alluvial cyclicity (e.g., Wright and Marriott 1993;Shanley and McCabe 1994;Schwans 1995;Quirk 1996;Kraus and Aslan 1999), uncertainties often associated with the correlation of alluvial cycles with coeval marine units, along with the potential for destructive (or constructive) overprinting by tectonic or climatic events of varying frequency and magnitude, make confirmation of a eustatic-sea-level mechanism difficult (Posamentier and Weimer 1993;Shanley and McCabe 1994;Ethridge et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A second and very important factor to consider is the proximity of each study area to the Tertiary structural axis of the Bighorn Basin. Computer simulation models (Bridge and Leeder, 1979) as well as field examples (e.g., Read and Dean, 1982) of alluvial architecture have demonstrated that overbank deposits tend to be concentrated along basin margins where subsidence is relatively slow. In contrast, channel sandstones accumulate in areas of maximum basin subsidence, typically along the structural axis, because the major streams are localized there.…”
Section: Intrabasinal Variabilitymentioning
confidence: 98%